A Feasibility Study of Moxibustion for Treating Anorexia and Improving Quality of Life in Patients With Metastatic Cancer: A Randomized Sham-Controlled Trial - Ju-Hyun Jeon KMD, PhD; Chong-Kwan Cho KMD, PhD; So-Jung Park KMD, PhD; Hwi-Joong Kang KMD, PhD; Kyungmin Kim KMD; In-Chul Jung KMD, PhD; Young-Il Kim KMD, PhD; Suk-Hoon Lee PhD; Hwa-Seung Yoo KMD, PhD (Integrative Cancer Therapies, 2017)
Objective . The aim of this study was to determine the feasibility, acceptability, and safety of using moxibustion for treating anorexia and improving quality of life in patients with metastatic cancer. Methods . We conducted a randomized sham-controlled trial of moxibustion. Sixteen patients with metastatic cancer were recruited from Daejeon, South Korea. The patients were randomly placed into a true or a sham moxibustion group and received 10 true or sham moxibustion treatments administered to the abdomen (CV12, CV8, CV4) and legs (ST36) over a 2-week period. Outcome measures included interest in participating in the trial, identification of successful recruitment strategies, the appropriateness of eligibility criteria, and compliance with the treatment plan (ie, attendance at treatment sessions). Clinical outcomes included results of the Functional Assessment of Anorexia/Cachexia Therapy (FAACT), answers on the European Organization for Research and Treatment of Cancer 30-item core quality of life (EORTC QLQ-C30) questionnaires, scores on the visual analogue scale (VAS), and the results from blood tests and a safety evaluation. Results . Moxibustion was an acceptable intervention in patients with metastatic cancer. Compliance with the treatment protocol was high, with 11 patients completing all 10 treatments. No serious adverse events related to moxibustion occurred, but 4 patients in the true moxibustion group reported mild rubefaction, which disappeared in a few hours. Conclusion . This study suggests that moxibustion may be safely used to treat anorexia and improve quality of life in patients with metastatic cancer. However, further research is needed to confirm this result.